2010
DOI: 10.1093/rheumatology/keq313
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study identifies two novel susceptibility loci PRKCB and 8p11.21 for systemic lupus erythematosus

Abstract: Our findings provided novel insights into the genetic architecture of SLE and emphasized the contribution of multiple variants of modest effect. Further study focused on PRKCB, 8p11.21, should advance our understanding on the pathogenesis of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…TNIP1 (TNFAIP3 interacting protein 1) , encoding the A20-interacting protein, has also been associated with the risk of SLE 47 48. Additional genes within the NFκB pathway associated with SLE susceptibility include: SLC15A4 (solute carrier family 15, member 4) encoding a peptide transporter that participates in NOD1-dependent NFκB signalling;48 PRKCB (protein kinase C, β), which is involved in B-cell receptor-mediated NFκB activation;54 and UBE2L3 (ubiquitin-conjugating enzyme E2L 3), encoding the enzyme UBCH7, which participates in the ubiquitination of an NFκB precursor, and may play a role in cell proliferation 55. A risk haplotype of UBE2L3 confers increased UBCH7 expression in patients with SLE;56 a variant contained in this haplotype has been associated with the presence of anti-dsDNA antibodies 15…”
Section: Genetic Variation Of the Nfκb Pathwaymentioning
confidence: 99%
“…TNIP1 (TNFAIP3 interacting protein 1) , encoding the A20-interacting protein, has also been associated with the risk of SLE 47 48. Additional genes within the NFκB pathway associated with SLE susceptibility include: SLC15A4 (solute carrier family 15, member 4) encoding a peptide transporter that participates in NOD1-dependent NFκB signalling;48 PRKCB (protein kinase C, β), which is involved in B-cell receptor-mediated NFκB activation;54 and UBE2L3 (ubiquitin-conjugating enzyme E2L 3), encoding the enzyme UBCH7, which participates in the ubiquitination of an NFκB precursor, and may play a role in cell proliferation 55. A risk haplotype of UBE2L3 confers increased UBCH7 expression in patients with SLE;56 a variant contained in this haplotype has been associated with the presence of anti-dsDNA antibodies 15…”
Section: Genetic Variation Of the Nfκb Pathwaymentioning
confidence: 99%
“…In recent years, understanding of SLE’s genetic etiology has been transformed by GWASs, with the largest study in Europeans3 (4,036 cases and 6,959 controls) finding evidence of association at 41 autosomal loci. Meanwhile, two published GWASs4,5 in Chinese populations and follow-up studies in Asians610 found association at 31 loci, 11 of which are not published for Europeans. Thus 52 SLE disease-susceptibility autosomal loci have been mapped by GWASs in these two populations.…”
mentioning
confidence: 99%
“…It is possible therefore that abnormalities in PKC activity induced by one or more of these polymorphisms may lead to altered T-cell function. PRKCA has been reported to be associated with MS risk in UK, Finish and Canadian populations,31 32 and PRKCB and PRKCH had been associated with the risk of similar autoimmune diseases including systemic lupus erythematosus (SLE)33 and rheumatoid arthritis 34 35. In rheumatoid arthritis, PRKCH messenger RNA was expressed at high levels in T cells and was significantly down-regulated during immune response 34…”
Section: Discussionmentioning
confidence: 99%